Maternal complications and adolescent pregnancy in Latin America: A systematic review and meta-analysis: Complicaciones maternas y embarazo adolescente en América Latina: Revisión sistemática y metaanálisis - Oviedo Mendoza, Maria A. (2024)
ABSTRACT Objective: To assess whether maternal complications are a risk in adolescent pregnancy in Latin America and the Caribbean during the period 2012 to 2021. Methods: A systematic search was carried out in 6 databases: PubMed, SCOPUS, Web of Science, EMBase, LILACS and Scielo. The articles included were from Latin American countries and had any of the following variables: preeclampsia, eclampsia, puerperal hemorrhage and puerperal sepsis published from 2012 to 2021 and comparing pregnant adolescents and adults. Articles that did not present separate findings from Latin America and/or the Caribbean, that the full version was not available, and that were focused on patients with a specific disease were excluded. For risk of bias, the Newcastle-Ottawa Scale Case-Control Studies was used. The summary measure used was the Odds Ratio with a 95% confidence interval for each study. Results: 4 studies were included. The risk of preeclampsia in pregnant adolescents and postpartum hemorrhage (OR = 0.86, 95% CI 0.74 – 0.99) were not evidenced (OR = 0.93, 95% CI 0.69 – 1.25). On the other hand, the risk of eclampsia (OR = 2.43, 95% CI 1.29 – 4.58) in pregnant adolescents was shown, but with high heterogeneity between studies (I2 = 76%). Conclusions: A risk of eclampsia was evidenced in pregnant adolescents, but not in preeclampsia nor postpartum hemorrhage. However, these results should be taken with caution. Protocol record: CRD42021286725 (PROSPERO)